“Not Entirely Myself”: Young Women’s Verbalized Experiences of Self in Social Context - Almonaitienė, Junona S.; Paulauskaitė, Rasa (Psichologija, 2025)
The aim of the qualitative research presented in the article was to disclose young adult women’s experience of Self in a social context, which was inspired by a wider problem of subjectively experienced interiority in young adults. In the introduction, the authors clarify their understanding of the Self and justify the relevance of the empirical study. The acquired data consists of 6 semi-structured interviews with 6 well-educated unmarried Lithuanian women of an average age of about 23. Reflexive thematic analysis was applied to the data, which led to the extraction of 4 themes: Not entirely myself, Barriers to being open, Pursuit of authenticity, and Possibilities in society. The first two were interpreted as the disclosure of reticence-inducing forces, whereas the next two as the disclosure of inclination to openness. Thus, the entirety of the data led to the identification of an internal dilemma. The abundant 2nd theme induced thinking about the strong feeling of the pressure of social environment characteristic to young women. However, the study cannot answer the question whether the dilemma is specifically related to gender, age, education, as well as other social and cultural characteristics. As the dilemma may be related to subjective wellbeing, experiencing loneliness, social phobias or excessive conformity, further research can be initiated on the basis of this study. The overall impression from the transcripts also allows suggesting that the participants had experience of their inner Self as persistent phenomena, the essence of a personhood, which is not reducible to the totality of social roles, self-esteem, self-efficacy, and other aspects of the Self.
Keywords: young adult; women; reflexive thematic analysis; Self; self-disclosure; feminist studies